ANTIBACTERIAL AND CYTOGENETIC EFFECT OF Cassia italica LEAF EXTRACT ON ALBINO MALE MICE - Al-Naimy, Ebtehal H; Al-Amery, Maythem M; Al-Azy, Ruqia M (Al-Nahrain Journal of Science, 2010)
This study was designed to evaluate the antibacterial and cytogenetic effect of Cassia italica(Senna) on metaphase index and micronucleous formation in polychromatic erythrocytes of bonemarrow cells of mice. Results showed that Cassia italica leaves methanolic extract caused asignificant inhibition in growth of E.coli and Staphylococcus auerous and Candida albicansespecially at high concentrations in comparison with the negative control (Distilled water) andpositive controls (Tetracycline). On the other hand the results showed that Cassia italica extractcaused a significant increase in metaphase index and a significant decrease in micronucleousformation in bone marrow of mice in comparison with the negative control (Distilled water) andpositive controls (Cyclophosphomide).